2021
DOI: 10.3390/biomedicines9020162
|View full text |Cite
|
Sign up to set email alerts
|

The Lectin-Like Domain of Thrombomodulin Inhibits β1 Integrin-Dependent Binding of Human Breast Cancer-Derived Cell Lines to Fibronectin

Abstract: Thrombomodulin is a molecule with anti-coagulant and anti-inflammatory properties. Recently, thrombomodulin was reported to be able to bind extracellular matrix proteins, such as fibronectin and collagen; however, whether thrombomodulin regulates the binding of human breast cancer-derived cell lines to the extracellular matrix remains unknown. To investigate this, we created an extracellular domain of thrombomodulin, TMD123-Fc, or domain deletion TM-Fc proteins (TM domain 12-Fc, TM domain 23-Fc) and examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…A flow cytometric examination confirmed the absence of β1 integrin in the KO cells (Figure 5A). S1 binding of β1-KO cells was completely abolished, compared to that of β1-control cells (i.e., mock transfectants) [16] (Figure 5B), even though β1-KO cells retain αV integrin expression (Figure 5A). These results have revealed that β1 integrins can support binding to S1 protein independently of αV integrins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A flow cytometric examination confirmed the absence of β1 integrin in the KO cells (Figure 5A). S1 binding of β1-KO cells was completely abolished, compared to that of β1-control cells (i.e., mock transfectants) [16] (Figure 5B), even though β1-KO cells retain αV integrin expression (Figure 5A). These results have revealed that β1 integrins can support binding to S1 protein independently of αV integrins.…”
Section: Resultsmentioning
confidence: 99%
“…To further validate the specific interaction of β1 integrin with S1 protein, we utilized a β1 integrin knockout (KO) clone of a human breast cancer cell line (MDA-MB-231) that we previously established using CRISPR/Cas9 [16] as a model cell. A flow cytometric examination confirmed the absence of β1 integrin in the KO cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations